FRI0043 Synovial Mast Cells Correlate with Local and Systemic Inflammation and Are Functionally Associated with Ectopic Lymphoid Structures in Patients with Early Rheumatoid Arthritis. (15th July 2016) - Rivellese, F.; Humby, F.; Kelly, S.; Nerviani, A.; Mauro, D.; Rocher-Ros, V.; El Shikh, M.E.; de Paulis, A.; Marone, G.; Pitzalis, C.
Abstract : Background: Mast cells (MCs) are immune cells present in the synovial membrane, and many evidences suggest that they contribute to the inflammatory response in Rheumatoid Arthritis (RA). However, their exact role in the pathogenesis of RA is still controversial. In particular, their presence in synovia and their association with the various histological patterns (pathothypes) described in RA have never been analysed systematically. Objectives: To evaluate the presence of MCs in the synovial membrane of early RA patients and their correlation with synovial inflammation and cellular infiltration. Methods: Sections of paraffin embedded synovial tissue obtained by ultrasound-guided synovial biopsy from DMARD-naïve patients with early (<12 months) RA (n=90) were stained with H&E and underwent semi-quantitative (SQ) scoring (0–9) to determine the degree of synovitis. Sequentially cut sections were stained by IHC for CD117+ MCs and immune cells (CD20+ B cells, CD3+ T cells, CD68+ macrophages and CD138+ plasma cells). Upon SQ scoring (0–4), sections were stratified into synovial pathotypes according to the degree of immune cell infiltration: (i) Lymphoid- grade 2/3 B cell aggregates, CD20≥2 and/or CD138>2 ii) Myeloid- CD68 SL≥2, CD20≤1 and/or CD3≥1, CD138≤2 and iii) Fibroid- CD68 SL<2 and CD3, CD20, CD138<1). Additionally, cellular interactions were assessed by double IF in tonsils and in RA synovia (n=6). Finally, naïve B cells isolated from tonsils were co-cultured with MCs. Results: MCs were positively correlated with synovial inflammation (rS =0.657) and infiltrating T cells (rS =0.629), B cells (rS =0.666), macrophages (lining: rS =0.502; sub-lining rS =0.454) and plasma cells (rS =0.623), p<0.0001. In particular, synovial MCs were significantly higher in patients with a lymphoid pathotype (mean MC density in lymphoid 41.06/mm 2 Vs fibroid/myeloid 11.66/mm 2, p<0.0001). Similarly, when patients were stratified according to MC number, the proportion of lymphoid pathotype was significantly higher in patients with high vs intermediate vs low MC count (83.9% vs 44.8% vs 10.3%, respectively, p<0.0001). Double immunofluorescence showed MCs bordering the germinal centres in secondary lymphoid organs and in close contact with B and T cell aggregates in synovia. Finally, MCs supported naïve B cells survival, proliferation, and differentiation in vitro, as demonstrated by the increased AID expression and the induction of IgG class switching upon co-culture of B cells with MCs. Conclusions: Our study demonstrates that MCs strongly associate with the lymphoid synovial pathotype in early RA patients. Their ability to support B cell survival, activation and differentiation in vitro suggests that they may contribute to functional activation of lymphoid aggregates in vivo. Additional studies are warranted to establish the role of MC interaction with B cells and assess their usefulness as biomarker for patient stratification in RA. Acknowledgement: The research leading to these results has received funding from the People Programme (Marie Curie Actions) of the European Union's Seventh Framework Programme (FP7/2007–2013) under REA grant agreement n° 608765 Disclosure of Interest: None declared